Santa tartaruga! Invenções e mudanças ontológicas no litoral norte do Espírito Santo - Fontinelli, Davi Scárdua (2016)
This text is the result of field research conducted during the months of March and November of 2015 in the villages of Regência and Povoação, both situated in the State of Espírito Santo, Brazil. The goal here is make some contributions to the knowledge about human and nonhuman relationships in places where environmental conflicts involving the management and conservation of “charismatic" wildlife take place. For this purpose, I seek to identify movements, trends, conventions, categories and differences shared, or not, by the participants of the many spaces and times in which the fieldwork took place. Searching for the possibility of an empirical analysis, I discussed (without restricting myself in it) the case of sea turtles in the north coast of Espírito Santo (ES). More precisely, I checked the different ways in which local actors such as scientists, governmental and non-governmental experts invent their relations with the turtles, in the midst of such conflicts. Most of these agents are linked to the region’s major environmental project in activity, the Project for Protection of Sea Turtles - TAMAR. After fieldwork and the reading of the gathered bibliography material, it was possible to apprehend the great variety and complexity that encompasses the relationships, the ancient and contemporary ones, between humans and turtles. Considering the empirical case hereof, I highlight that the north coast of the state of Espírito Santo is facing a time marked by political, economic and environmental dissensions, all related to the use of resources and the local landscape. Therefore, I believe sea turtles can be seen as irradiation and convergence points of numerous relationships that, directly or indirectly, are relevant to the ramifications of such tensions. Moreover, in the mentioned groups, these relationships did not came forward in statics and/or homogeneous forms.